Bone metastasis risk and prognosis assessment models for kidney cancer based on machine learning - Ji, Lichen; Zhang, Wei; Huang, Jiaqing; Tian, Jinlong; Zhong, Xugang; Luo, Junchao; Zhu, Senbo; He, Zeju; Tong, Yu; Meng, Xiang; Kang, Yao; Bi, Qing (Frontiers in Public Health, 2022)
Abstract Background: Bone metastasis is a common adverse event in kidney cancer, often resulting in poor survival. However, tools for predicting KCBM and assessing survival after KCBM have not performed well. Methods: The study uses machine learning to build models for assessing kidney cancer bone metastasis risk, prognosis, and performance evaluation. We selected 71414 kidney cancer patients from SEER database between 2010-2016. Additionally, 963 patients with kidney cancer from an independent medical center were chosen to validate the performance. In the next step, eight different machine learning methods were applied to develop KCBM diagnosis and prognosis models while the risk factors were identified from univariate and multivariate logistic regression and the prognosis factors were analyzed through Kaplan-Meier survival curve and Cox proportional hazards regression. The performance of the models was compared with current models, including the logistic regression model and the AJCC TNM staging model, applying receiver operating characteristics, decision curve analysis, and the calculation of accuracy and sensitivity in both internal and independent external cohorts. Results: Our prognosis model achieved an AUC of 0.8269 (95%CI: 0.8083 - 0.8425) in the internal validation cohort and 0.9123 (95%CI: 0.8979 - 0.9261) in the external validation cohort. In addition, we tested the performance of the extreme gradient boosting model through decision curve analysis curve, Precision-Recall curve, and Brier score and two models exhibited excellent performance. Conclusion: Our developed models can accurately predict the risk and prognosis of KCBM and contribute to helping improve decision-making.